Optimization of the Baggage Loading and Unloading Equipment - Volt, Jiří; Stojić, Slobodan; Had, Petr (Transportation research procedia (Online), 2022)
The subject of this paper is a development of the mathematical model for determining the number of airport equipment dedicated for the baggage loading and unloading. This model can predict the demand for the carts and loaders based on the input data. Based on this prediction, the optimal number of equipment is calculated. The ability to predict the required amount of the airport vehicles in advance could make the aircraft loading and unloading process more efficient. It would also allow better capacity planning of the ground handling system. In the first part, the current state and procedures for baggage loading and unloading are analysed. Based on the theory of linear programming, a mathematical model is created to predict a demand for equipment and calculate the optimal number needed to handle all flights. This model is subsequently implemented in the created software, which allows to perform experiments with the proposed mathematical model. Operation data from Václav Havel Airport Prague are used to verify the correct functioning of the model.